Втрачені храми Борисполя (за експедиційними матеріалами Поліни Кульженко і Марії Вязьмітіної 1924 року) - Ходак, І.О. (Сіверщина в історії України, 2020)
Під час колективної одноденної екскурсії (експедиції), проведеної в червні 1924 року студентами Київського археологічного інституту під орудою Данила Щербаківського до Борисполя (нині – місто Київської області), Поліна Кульженко (1891/1892–1982) і Марія Вязьмітіна (1896–1994) обстежили та описали три тамтешні церкви – Михайлівську, Різдва Богородиці й так звану Книшівську (кладовищенську). З огляду на втрату згаданих храмів у 1930-х роках, у статті систематизовано та введено до наукового обігу відомості про час спорудження перебудови, матеріал, конструктивні й стильові особливості, планувальну структуру храмів і дзвіниць, їхніх фундаторів, а також про іконостаси, окремі образи, хрести, шати, корогви, що зберігалися в них. During a joint daylong excursion (expedition) to Boryspil (now the city of Kyiv Region) conducted in June 1924 by students of the Kyiv Archeological Institute under the steerage of Danylo Shcherbakivskyi, Polina Kulzhenko (1891/1892–1982) and Mariia Viazmitina (1896– 1994) surveyed and described three churches there, notably St. Michael’s Church, the Church of the Nativity of the Virgin, and the so-called Knyshove Church (at the cemetery). Along with other materials of the expedition’s participants, the report Churches of the Town of Boryspil prepared by them has also been preserved in a Danylo Shcherbakivskyi personal fund at the scientific archives of the Institute of Archeology of the National Academy of Sciences of Ukraine. In view of the loss of the mentioned churches in the 1930s, the article systematizes and scientifically introduces information on the time of construction / reconstruction, material, design philosophy and stylistic features, as well as planning structure of the churches and adjacent bell towers, and their founders. It also deals with iconostases, individual icons, crosses, metal shield of an icon and gonfalons stored in churches. Particularly noteworthy are the inserted inscriptions, noted by the researchers, both on the lectern of St. Michael’s Church (names of the initiators of production and the date of creation – 1798 – of the previous iconostasis), and on three wooden crosses with silver details kept at the Church of the Nativity of the Virgin (dates of creating and remodelling crosses, names of donators). Verbal descriptions of the monuments are supplemented with sketches of four on-dome crosses of the three temples, as well as of the belfry of the Church of the Nativity of the Virgin, apart from the western and southern facades of the Knyshove Church. In addition to valuable information on sacred monuments, the archival document in question allows us both to deepen the understanding of the process of professional formation of Polina Kulzhenko and Mariia Viazmitina, who would later engage in the development of leading Kyiv museums, and generally the training of art historians at the Kyiv Archeological Institute.